Reduction in Absorption Edge of the Digital-Alloyed ZnMnO Thin Films Grown Using Atomic Layer Deposition. (30th July 2020) - Ghods, Amirhossein; Zhou, Chuanle; Ferguson, Ian T.
Abstract : Transition metal doping has been used as a common approach for tuning the bandgap energy of zinc oxide (ZnO) based materials. In this work, manganese-doped ZnO (ZnMnO) thin films were grown using the atomic layer deposition (ALD) and used to study the effect of manganese incorporation in ZnO films. The effect of digital alloying on reducing the absorption edge of the ZnMnO thin films is studied by changing the ZnO to MnO cycle ratio during each ALD super-cycle. Room-temperature optical spectroscopic characterization showed a significant reduction in bandgap energy from 3.30 eV for pure ZnO to around 2.25 eV for the ZnMnO thin films with the ZnO:MnO cycle ratio of 5:3. This is likely due to the effect of band bending, which can be related to the formation of Mn-related impurity energy levels in the band structure of the ZnMnO. A notable change in the deduced optical bandgap energy was observed by further increasing the growth sequence of ZnO and MnO layers in each super-cycle. This was attributed to less Mn incorporation in these films caused by a highly suppressed ALD growth rate of MnO on ZnO. The observed changes in the optical bandgap of ZnMnO thin films demonstrates the potential for using them as the active light-absorbing or the window layer in high-efficiency multi-junction solar cells or photodiodes.